2016
DOI: 10.1590/0031-1049.2016.56.02
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian diversity in the Savanna from Peru, with three new addictions from country

Abstract: Bahuaja Sonene National Park protects the unique sample of subtropical humid savannas in Peru, which are known as "Pampas del Heath" with 6,136 hectares of area. Many endangered species and/or endemic from savannas occur there, however studies about the diversity of mammals in Pampas del Heath are limited and only three assessments there have been carried out since mid-1970s. Therefore we surveyed mammals in three habitat types of the Pampas del Heath (savanna, ecotonal area and forest) during late 2011. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
3
0
4
Order By: Relevance
“…Our report for M. coibensis is 72 km northwest from the closest previously known locality in Pampas del Heath (Medina et al 2016). Because M. coibensis can be confused with M. molossus detailed examination is recommended (Diaz 2011; Gregorin et al 2011;.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our report for M. coibensis is 72 km northwest from the closest previously known locality in Pampas del Heath (Medina et al 2016). Because M. coibensis can be confused with M. molossus detailed examination is recommended (Diaz 2011; Gregorin et al 2011;.…”
Section: Discussionmentioning
confidence: 96%
“…Molossus coibensis Allen, 1904 is a monotypic species distributed from Mexico, through Central America, to the southeast of Brazil (Eger 2008;Wilson and Mittermeier 2019). In Peru, Medina et al (2016) reported this species in savannas from the Pampas del Heath, which is the southernmost record in Peru. It also has been recorded 19 miles [~30.6 km] south from Tingo María in Huánuco (Dolan 1989), in a downtown building in Iquitos, Loreto (Díaz 2011), and at Jenaro Herrera (Loureiro et al 2018a), also in Loreto.…”
Section: Introductionmentioning
confidence: 95%
“…The recent surveys in BSNP carried out by Luján and Venegas (2014) and Medina et al (2016) provided a range extension of the amphibian Pristimantis divnae, and new records of mammals for Peru. Likewise, Carrasco et al (2019) described a new viperid species which has been recorded only in BSNP.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, varios cambios taxonómicos en mamíferos han sido reportados en este corto tiempo que afectan tanto el número como el contenido de especies y que hacen necesaria una actualización. La lista de riqueza de especies más completa con 508 especies (Pacheco et al 2009) fue actualizada recientemente con un total de 569 especies (Medina et al 2016b, Pacheco et al 2020a) (Fig. 1), mostrando un incremento constante de la diversidad de especies con respecto a las listas anteriores de Tovar (1971) con 378 especies, McNeely et al (1990) con 361 especies, Pacheco et al (1995) con 460 especies y Pacheco et al (2009) con 508 especies (Fig.…”
Section: Introductionunclassified
“…Dada la complejidad y el esfuerzo de mantener actualizada estas listas, cada vez son más los países que encargan este objetivo a asociaciones profesionales, como el caso de Ecuador (Tirira et al 2020) y Colombia (Ramírez-Chaves et al 2021), pero esta alternativa no se ha sugerido aún en el Perú; quedando esta responsabilidad a la iniciativa y recursos de algunos investigadores (e.g. Medina et al 2016b, Pacheco et al 2020a, Velazco 2021.…”
Section: Introductionunclassified